Postoperative Concurrent Chemoradiotherapy for Locally Advanced Thoracic Esophageal Squamous Cell Carcinoma: A Phase II Clinical Trial - Li, Hui; Gu, Dayong; Du, Mingyu; Zhou, Guoren; Zhang, Zhi; Ye, Jinjun (Frontiers in Oncology, 2022)
Background: This study aims to investigate the efficacy and safety of postoperative intensity-modulated radiotherapy (IMRT) covering partial regional lymph node areas combined with chemotherapy for locally advanced thoracic esophageal squamous cell carcinoma patients. Methods: This was a single-center, single-arm phase II clinical trial that began in 2014. Patients who underwent radical transthoracic resection within 3 months and were histologically confirmed esophageal squamous cell carcinoma (pT3-4 or N+, M0 determined according to AJCC Guidelines, Edition 7) were recruited. Postoperative radiotherapy was performed with a total dose of 50.4Gy in 28 fractions using IMRT. Clinical target volumes (CTVs) included tumor bed, anastomosis, bilateral supraclavicular region, and superior mediastinal lymph nodes. Synchronous chemotherapy for 2 cycles (paclitaxel 150mg/m2, day1; Cisplatin 25mg/m2, day1-3; every 4 weeks), followed by 2 cycles of consolidation chemotherapy with the same regimen. The primary endpoint was the 2-year local control rate, and the secondary endpoints were overall survival (OS) and adverse events (AEs). Results: A total of 75 eligible patients were included from 2014 to 2017. The 2-year LRFS rate, as the primary endpoint, was 73.3%. The 1-year and 3-year OS rates were 88.0% and 68.0%, respectively. Local recurrence occurred in 13/75 (17.4%) patients, of which 2.7% (2/75) were extra-target lymph nodes. Grade 4 adverse events reported in this study included 10 cases (13.3%) of neutropenia, 1 case (1.3%) of anemia, and 2 cases (2.7%) of thrombocytopenia, without toxic-related deaths. Almost all (96%) patients completed the entire postoperative radiotherapy course, and 62 (82.7%) patients completed at least 2 cycles of chemotherapy. Conclusion: Postoperative IMRT (clinical target volume including tumor bed, anastomosis, bilateral supraclavicular region, and superior mediastinal lymph nodes) combined with synchronous chemotherapy in patients with locally advanced thoracic esophageal squamous cell carcinoma was well tolerated, with a high local control rate and a low probability of recurrence outside the irradiation field.